Diversity and Composition of Gastrointestinal Helminths and Gram-Negative Bacteria of the West African Rainbow Lizard (Agama picticauda) in a Human-Modified Landscape: Implications for Conservation and Zoonosis - Benjamin Y. Ofori; Juliet M. Ewool; Rachel E. A. Asamoah; Philomina A. Adarkwah; Daniel Oduro (International Journal of Zoology)
Emerging infectious diseases are negatively impacting herpetofaunal populations globally, posing a major conservation threat. Anthropogenic perturbations of natural habitats may influence wildlife disease dynamics and spillover events. Although viral and fungal diseases of vertebrates have received considerable studies, there is scant information on the enteric bacteria and helminths of herpetofauna. Here, we assessed the gastrointestinal helminths and Gram-negative bacteria of the West African rainbow lizard (Agama picticauda) in a human-dominated landscape in Accra, Ghana. We used the flotation method and standard cultural, morphological, and biochemical methods, for helminths and bacteria, respectively. Four helminth species, Ascaris spp., Enterobius spp., Pharyngodon spp., and Oxyurid spp., were identified, with overall high (71.9%) prevalence. Ascaris spp. (χ2 = 33.33, p<0.001) and Pharyngodon spp. (χ2 = 14.5, p<0.001) were more prevalent in suburban lizards during the wet season than dry season. The prevalence of Ascaris spp. and Enterobius spp. was significantly higher (χ2 = 12.34, p<0.001) in urban than suburban lizards, while Oxyurid spp. was more prevalent (χ2 = 4.75, p=0.03) in the suburban lizards during the wet season. The gut bacteria identified (prevalence) were Escherichia spp. (86.5%), Enterobacter spp. (75.7%), Proteus spp. (67.6%), Shigella spp. (40.5%), Klebsiella spp. (21.6%), and Salmonella spp. (16.2%). The prevalence of Escherichia spp. and Proteus spp. was significantly higher (χ2 = 5.77–7.34, p=0.01–0.02) in suburban lizards than urban lizards during the wet season. Some Ascaris spp., Enterobius spp., Escherichia spp., Enterobacter spp., Shigella spp., and Salmonella spp. are found in humans. Our data can serve as baseline information for long-term monitoring studies of reptile-parasites-environment interactions in the Accra plains of Ghana. Further studies using molecular techniques are needed to ascertain the zoonotic helminths and bacteria of A. picticauda.